Ultraviolet Radiation on Innate Immunity and Growth of Broad‐Snouted Caiman ( Caiman latirostris ): Implications for Facilities Design - Siroski, Pablo Ariel (2011)
Sunlight is a key environmental factor in almost all ecosystems, and it is necessary for many physiological functions. Many vertebrates require ultraviolet radiation (UV) to perform different physiological processes. Artificial light is used to supplement UV in captive animals, through appropriate photoperiods and UV wavelengths. Previous studies reported that repeated exposure to artificial UV radiation may cause damage to the immune system. Taking into account the importance of UV effects and the serum complement system the relationship between them was investigated. The study lasted 90 days and was carried out in plastic chambers. Ninety six broad-snouted caiman (C. latirostris) were assigned to four treatment groups with two replicates each: total darkness (TD), eight-hours per day (8h) and sixteen hours per day (16h) of artificial UV/visible light exposure, and normal photoperiod of natural light (NP). Snout-vent length (SVL) was measured to determine animal growth. Hemolytic assays were performed to evaluate the effects of artificial UV/visible light TD and NP on the serum complement system. Results showed that animals grew more in the NP group. The capacity of C. latirostris serum to hemolyze sheep red blood cells was higher in the NP group than when they are maintained in constant light-dark cycles (8 and 16 hs) or in TD. These data demonstrate that artificial UV should be considered as a potential hazard for captive crocodilians if it is not properly managed, and these considerations should be taken into account in the general design of facilities for reptilian husbandry.